Poly (glycerol sebacate)-poly (ε-caprolactone) blend nanofibrous scaffold as intrinsic bio- and immunocompatible system for corneal repair. (1st March 2017) - Salehi, Sahar; Czugala, Marta; Stafiej, Piotr; Fathi, Mohammadhossein; Bahners, Thomas; Gutmann, Jochen S.; Singer, Bernhard B.; Fuchsluger, Thomas A.
Graphical abstract: Abstract: A major challenge in corneal tissue engineering and lamellar corneal transplantation is to develop synthetic scaffolds able to simulate the optical and mechanical properties of the native cornea. As a carrier, the graft scaffolds should provide the basis for anchorage, repair and regeneration. Although quite a number of scaffolds have been engineered to date, they have not been able to simultaneously recapitulate chemical, mechanical, and structural properties of the corneal extracellular matrix (ECM). Here, we examined different compositions of elastomeric biodegradable poly (glycerol sebacate) (PGS)-poly (ε-caprolactone) (PCL) nanofibrous scaffolds with respect to their cyto- and immunocompatibility. These scaffolds were semi-transparent with well-defined mechanical properties and direct positive effects on viability of human corneal endothelial cells (HCEC) and human conjunctival epithelial cells (HCjEC). Moreover, within 3 days HCEC established monolayers with the hexagonal morphology typical for this cell type. All PGS-PCL mixtures analyzed did not trigger effects in granulocytes, naïve and activated peripheral blood mononuclear cells (PBMCs). However, scaffolds with a higher content of PGS-PCL ratio showed the best cell organization, cyto- and immunocompatibility. Subsequently, this PGS-PCL composition could be used for further development of clinical constructs to support corneal tissue repair. Statement of Significance: In corneal tissue engineering a major challenge is the development of synthetic scaffolds with similar properties to native cornea. In our recent works, we introduced the biodegradable, polymeric nanofibrous scaffolds with similar optical and mechanical properties for corneal regeneration and here we examined the cyto- and immunocompatibility of biodegradable nanofibrous scaffolds in contact to white blood cells. Directing the alignment of human corneal cells by nanofibrous scaffolds and high viability of cells was detected by forming of endothelium monolayer with hexagonal morphology on the nanofibrous scaffold. In addition, our results for the first time show that these nanofibrous scaffolds did not trigger effects in white blood cells. These results highlight the considerable translational potential of the nanofibrous scaffolds to clinical applications.